2022
DOI: 10.1161/jaha.121.024226
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Quantitative Retinal Capillary Network and Myocardial Remodeling in Systemic Hypertension

Abstract: Background This study examined the associations between quantitative optical coherence tomography angiography (OCTA) parameters and myocardial abnormalities as documented on cardiovascular magnetic resonance imaging in patients with systemic hypertension. Methods and Results We conducted a cross‐sectional study of 118 adults with hypertension (197 eyes). Patients underwent cardiovascular magnetic resonance imaging and OCTA (PLEX Elite 900… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…By using built-in automatic OCTA softwares, OCTA can easily and quickly measure retinal and choroidal microvascular parameters, including VD and FAZ area. 10,[16][17][18][19][20] Moreover, with the recent introduction of SS-OCTA, the visualization of the choroid has been improved notably. The longer center wavelength of this device is less scattered by the RPE and less prone to low signal in the CC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using built-in automatic OCTA softwares, OCTA can easily and quickly measure retinal and choroidal microvascular parameters, including VD and FAZ area. 10,[16][17][18][19][20] Moreover, with the recent introduction of SS-OCTA, the visualization of the choroid has been improved notably. The longer center wavelength of this device is less scattered by the RPE and less prone to low signal in the CC.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, quantitative parameters of OCTA were measured using image processing softwares that require a considerable amount of time. 7,9,10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeung et al ( 25 ) reported that patients with CKD (eGFR<60 mL/min/1.73m 2 ) had lower parafoveal SCP-VD compared to those of control group ( p < 0.001), with eGFR strongly related with SCP-VD in multivariate-adjusted models. Observational cross-sectional studies ( 26 , 27 ) aimed at investigating the relationship between systemic risk factors and OCTA parameters in patients with systemic hypertension found a significant correlation between eGFR and retinal capillary density after adjusting for age, sex, and blood pressure, suggesting impaired renal function could be one of important risk factors in retinal microvascular alterations. Similarly, Zhuang et al ( 28 ) demonstrated that decreased SCP-VD was independently correlated with lower eGFR among T2DM patients, while other investigators ( 29 ) found a significant relationship between lower SCP-VD, SCP-PD, and higher UACR in T2DM patients after controlling for systemic and ocular parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The relations between various systemic diseases, including heart, and changes in ocular microvasculature has been a focus of studies in recent years [ 2 , 3 , 4 ]. Alternations in the thickness of the retina and its layers as well as changes in retinal microvasculature parameters was shown to be related to cardiovascular health [ 5 , 6 , 7 ]. Poplin et al, in 2018, developed an algorithm based on about 300,000 images of retinal fundus.…”
Section: Introductionmentioning
confidence: 99%